The application of english songs in improving early childhood language development at PAUD Harapan Bangsa Gemilang - Afdhalina Afdhalina; Novi Cynthia Yusnita; Abdul Zebar; Yustini Yustini (Jurnal Scientia, 2024)
Early childhood language development is very important during this period, one of which is by singing English songs. This research aims to find out English songs in improving the language development of early childhood. The method used in this research is descriptive qualitative, namely describing events in certain situations using data collection techniques in the form of observation, interviews and documentation. The results of this research are that songs used in English are able to attract children's interest in improving their language development. Apart from that, learning in the classroom becomes more enjoyable. So that children can receive learning well at school. In doing something new, children need direct guidance and examples from teachers as educators. As is the case at PAUD Harapan Bangsa Gemilang, it can be seen that the teacher is giving directions and modeling English songs which the children follow. Even children become interested in following what the teacher does. This happens because children find learning very enjoyable and do not feel burdened. So that children's language development can improve well.